Job Loss Guarantee Program Policy as Legal Protection for Terminated Workers Based on Job Creation Law Article 46 - Try Wahyu Widanarti; Abdul Rachmad Budiono; Budi Santoso (Universitas Airlangga, 2022)
To provide legal protection for workers who have experienced termination of employment, the government of Indonesia has issued a new policy in the form of Article 46 of Law No. 11 of 2020 concerning the Job Creation Law. This increases the type of protection for social security programs, namely the job loss guarantee program. This paper uses a juridical-normative research method. The results indicate that the legal protection policy for workers affected by termination of employment was not appropriate. Therefore, an amendment was made to Law Number 40 of 2004 concerning the National Social Security System. Specifically, Article 46A of the Job Creation Law states: